2019
DOI: 10.1002/jbmr.3850
|View full text |Cite
|
Sign up to set email alerts
|

Standard Versus Cyclic Teriparatide and Denosumab Treatment for Osteoporosis: A Randomized Trial

Abstract: In the absence of an intervening antiresorptive agent, cyclic administration of teriparatide does not increase bone mineral density (BMD) more than standard daily therapy. Because denosumab is a potent antiresorptive agent with a rapid off‐effect, we hypothesized that it might be the optimal agent to help maximize bone gains with cyclic teriparatide. In this 3‐year protocol, 70 postmenopausal women with osteoporosis were randomized to 18 months of teriparatide followed by 18 months of denosumab (standard) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Another study also indicated that treatment with the HD regimen (40 μg) showed clinically meaningful and rapid increase in hip and spine BMD compared with the SD regimen (20 μg) (Ramchand et al, 2020b). The cyclic regimen of teriparatide combined with denosumab appeared to be beneficial in improving BMD at 18 months, especially in the highly cortical skeletal sites, which was clinically relevant in patients at high imminent risk of fracture, particularly at nonvertebral sites (Cosman et al, 2020). Combination therapy with PTH and denosumab or ZOL seemed to achieve higher BMD gains compared to each agent alone (Leder, 2018;Kelly and Garapati, 2019;Anastasilakis et al, 2020).…”
Section: Combination Therapy Is Beneficial For Osteoporosis Treatmentmentioning
confidence: 94%
“…Another study also indicated that treatment with the HD regimen (40 μg) showed clinically meaningful and rapid increase in hip and spine BMD compared with the SD regimen (20 μg) (Ramchand et al, 2020b). The cyclic regimen of teriparatide combined with denosumab appeared to be beneficial in improving BMD at 18 months, especially in the highly cortical skeletal sites, which was clinically relevant in patients at high imminent risk of fracture, particularly at nonvertebral sites (Cosman et al, 2020). Combination therapy with PTH and denosumab or ZOL seemed to achieve higher BMD gains compared to each agent alone (Leder, 2018;Kelly and Garapati, 2019;Anastasilakis et al, 2020).…”
Section: Combination Therapy Is Beneficial For Osteoporosis Treatmentmentioning
confidence: 94%
“…Cyclical administration of 6 months of teriparatide followed by 6 months of denosumab for 36 months (3 cycles) versus 18 months of teriparatide followed by 18 months of denosumab produced hip and radius BMD benefits at 18 months but no significant differences at 36 months [ 70 ]. A comparison of subjects who transitioned from bisphosphonate to denosumab or teriparatide showed that hip BMD increased with denosumab over 2 years but was unchanged with teriparatide; anti-fracture efficacy data are not available [ 71 ].…”
Section: Denosumab In Clinical Practicementioning
confidence: 99%
“…56 Moreover, the cyclic teriparatide treatment with three cycles of teriparatide (6 months) to denosumab (6 months) was similar to standard sequential teriparatide (18 months) to denosumab (18 months) treatment in increasing the BMDs at spine, total femur, femoral neck and 1/3 radius. 57 On the other hand, in DATA-Switch study, co-treatment of teriparatide and denosumab for 24 months, followed by 24-month denosumab alone was more potent in increasing the BMDs at total hip, femoral neck and radius bone (but not lumbar spine) than sequential treatments with teriparatide (24 months) to denosumab (24 months) or vice versa.- 58,59 Similar findings were obtained in the DATA and DATA extension study, whereby the co-treatment of teriparatide and denosumab induced a greater increase in BMDs. 52,53 A summary of the anti-fracture effects of denosumab is presented in Table 1.…”
Section: Comparison Of the Fracture Risk Reduction Between Denosumab And Other Anti-osteoporotic Drugsmentioning
confidence: 99%